1982
DOI: 10.1111/j.1432-1033.1982.tb06788.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Dipeptidyl Peptidase IV from Human Placenta

Abstract: Human placenta is surprisingly rich in post-proline dipeptidyl peptidase activity. Among various cell fractions, microsomes have the highest specific activity. A homogeneous enzyme preparation is obtained in a six-step purification procedure. The final preparation appears homogeneous upon dodecyl sulfate electrophoresis, but analytical isoelectric focussing reveals various active bands with isoelectric points in the range of pH 3 -4. The enzyme is a glycoprotein containing about 30 carbohydrate. Treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
3

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 142 publications
(75 citation statements)
references
References 26 publications
2
70
0
3
Order By: Relevance
“…In addition, previous studies showed that purified DPP-IV proteins from various sources migrated at sizes corresponding to either dimer or tetramer/oligomer according to gel filtration experiments (19,(27)(28)(29)(30). To determine the physiologically relevant oligomerization state of DPP-IV, we performed chemical cross-linking in the DPP-IV-containing Caco-2 cells.…”
Section: Human Dpp-iv Protein Is a Dimer In Intact Cells And Inmentioning
confidence: 99%
“…In addition, previous studies showed that purified DPP-IV proteins from various sources migrated at sizes corresponding to either dimer or tetramer/oligomer according to gel filtration experiments (19,(27)(28)(29)(30). To determine the physiologically relevant oligomerization state of DPP-IV, we performed chemical cross-linking in the DPP-IV-containing Caco-2 cells.…”
Section: Human Dpp-iv Protein Is a Dimer In Intact Cells And Inmentioning
confidence: 99%
“…Assays were performed in 50 mM triethanolamineMC1, pH 7.8, at 37°C. Values of k,, were calculated using a molecular mass of 120 kDa for one identical subunit of the human placental DPP IV dimer (Piischel et al, 1982). GLP-1(7-36)amide shows substrate inhibition above 50 pM, catalytic constants ( 2 SD) were calculated from the linear ranges of Lineweaver-Burk plots.…”
Section: Separation Of Dpp IV Cleavage Products Of Gastric Inhibitorymentioning
confidence: 99%
“…Lys-pyrrolidide was a gift from Dr. Mike Schutkowski, Martin-Luther-Universitat Halle/ Saale, Germany. Dipeptidyl-peptidase IV was purified from human placenta and free of contaminating proteases (Piischel et al, 1982).…”
Section: Peptides Inhibitors and Enzymesmentioning
confidence: 99%
“…The C-terminal serine protease domain is homologous to ␣͞␤-hydrolases. Dimerization was found to be a prerequisite for enzyme activity (6), albeit enzymatically active heterodimers with the fibroblast activation protein ␣ (FAP ␣) are observed (7). DP IV is a serine aminopeptidase that cleaves preferentially Xaa-Pro dipeptides from oligopeptides with typical length of Ͻ30 aa, but tolerates other small residues at P 1 -position (8).…”
mentioning
confidence: 99%